(untitled) (Scottish Archaeological Internet Reports, 2009)
Several pieces of pumice-like material were recovered. All come from Applecross and the sea loch area. In addition, many of the beaches in the area contain a pumice-like material of unknown origin. Several samples of this were collected and analysed in more detail in order to try to shed light on the nature of this material. Although none turned out to be pumice it is hoped that this report will stimulate further work on similar samples and proved a check on the superficial identification of pumice from archaeological sites.